2010
DOI: 10.1038/mt.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dog Microdystrophin in Mouse and Dog Muscles by Gene Therapy

Abstract: Duchenne muscular dystrophy (DMD) is characterized by the absence of dystrophin. Several previous studies demonstrated the feasibility of delivering microdystrophin complementary DNA (cDNA) into mouse and normal nonhuman primate muscles by ex vivo gene therapy. However, these animal models do not reproduce completely the human DMD phenotype, while the dystrophic dog model does. To progress toward the use of the best animal model of DMD, a dog microdystrophin was transduced into human and dystrophic dog muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Subsequently, these cells were transplanted in mouse muscles and transgene-positive fibers were observed in the treated muscles. 135 In addition to the possibility of delivering an internally deleted dystrophin, the lentiviral vector may be used to induce exon skipping as well. A lentiviral vector coding for the U7 snRNA gene modified to induce the skipping of human dystrophin exon 51 was designed.…”
Section: Lentivirusmentioning
confidence: 99%
“…Subsequently, these cells were transplanted in mouse muscles and transgene-positive fibers were observed in the treated muscles. 135 In addition to the possibility of delivering an internally deleted dystrophin, the lentiviral vector may be used to induce exon skipping as well. A lentiviral vector coding for the U7 snRNA gene modified to induce the skipping of human dystrophin exon 51 was designed.…”
Section: Lentivirusmentioning
confidence: 99%
“…We found that ZFN-modified myoblasts that express the microdystrophin gene were as competent as their non-modified counterparts in forming muscle fibers when transplanted in the tibialis anterior muscle of immune-deficient NSG mice ( Figure 5d,e ). Myoblasts engraftment was determined by immunohistochemistry performed on muscle cryosections stained with an antibody against the V5 epitope, which was fused at the 3′ end of the microdystrophin gene 24 ( Figure 2a ). Indeed, we found the ratio of V5-positive fibers over the total number of fibers formed (as detected by staining for the full-length human dystrophin) to be similar to the level of targeted gene addition observed before the transplantation ( Figure 5e ).…”
Section: Resultsmentioning
confidence: 99%
“…2,5 A ZFN-expressing virus was generated from chimeric human adenovirus 5 vectors containing fiber shaft and knob domains of human species B adenovirus (Ad5/F35). 5 IDLV carrying GFP, microdystrophin-V5 24 or MGMT P140K -2A-GFP donor cassettes were generated from the HIV-derived self-inactivating third-generation transfer construct pCCLsin.cPPT.hPGK.X.BGHpA using an integrase-defective packaging plasmid. 2,36 IDLV stocks were prepared as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…90 This study was extended by lentiviral-mediated transduction of canine mDYS in human and GRMD MDSCs prior to transplantation into mdx and GRMD by either intramuscular injection or electrotransfer. 91 Lentiviral vectors have also been used to demonstrate that mDYS-transduced autologous mdx4cv SC 92 and GRMD MABs 93 can regenerate dystrophin-positive myofibers in vivo. However, it is important to note that although the level of mDYS-expressing fibers was sufficient in treated GRMD dogs to ameliorate dystrophic morphology (5%-50%), their clinical performance remained poor, in direct contrast to the phenotypical improvement observed using systemic delivery of unmodified donor cell MABs 93 (see section on cell-based therapeutics.…”
Section: Dovepressmentioning
confidence: 99%